Assessing societal perceptions and adaptive responses to GLOF and related hazards in the upper Indus Basin, Pakistan - Asim Qayyum Butt; Donghui Shangguan; Abhishek Banerjee; Rashid Farooq; Rongjun Wang; Muhammad Afzal; Da Li; Meixia Wang; Jinkui Wu; Tianding Han; Li Yaojun; Amjad Ali Khan (Discover Applied Sciences)
Abstract Pakistan has experienced a notable increase in the frequency and intensity of weather-related events and natural hazards, including floods, driven by multiple factors. This study aims to bridge the gap between hydrological sciences and community resilience by evaluating the impacts of natural hazards in the Upper Indus Basin (UIB), Pakistan. The research aligns with Sustainable Development Goal 13: Climate Action, emphasizing the importance of proactive measures in addressing climate challenges. The factors considered include climate change, examining early warning systems and flood risk management, hydrological forecasting and policies, local awareness, preparedness, and adaptive responses to GLOFs and other natural hazards in UIB, including floods, earthquakes, and landslides. By using the scientific questionnaire from well-educated respondents, this study assesses local awareness, preparedness, and adaptive responses to natural hazards in the UIB. The study is also backed by descriptive analysis, frequency analysis, Relative Importance Index, and correlation analysis. The findings highlight significant public awareness and training gaps, with 30.55% of respondents highlighting deficiencies in existing hazard management practices. Additionally, 98.15% of participants gave their opinion that climate change and global warming are major contributors to GLOF events, and 78.70% reported frequent flood encounters over the past ten years. The study advocates aligning Pakistan's hazard management guidelines with international standards to optimize environmental monitoring, disaster management, and communication systems. The research offers critical insights for community resilience and sustainable climate management, providing a pathway for more informed and efficient regional decision-making.